Mendesain dan Menerapkan Manajemen Stok (Cadangan) Pangan sebagai Upaya Meningkatkan Ketahanan Pangan di Desa Pabelan Sukoharjo - Imron Rosyadi; Noer Sasongko (Universitas Muhammadiyah Surakarta, 2010)
The problem faced by the village government Pabelan is: (i) What is the ‘landof the village treasury managed optimally in supporting the food needs for the people(households) in Pabelan Village?, (ii) Is rice farm in the village that has been done inan efficient Pabelan?, (iii) How is the formulation of government’s role model villagethrough ‘barn institution (LPD)’ village in the management of food reserves in thevillage Pabelan? And (iv) How is the formulation of models of sustainable management of food reserves to ensure the establishment of food sovereignty (the production, availability and access to food) in the Village Pabelan. In general, the purpose of this activity is to design a management policy of food security (rice) at the village level associated with efforts to optimize the utilization of land and the village treasury LPD strategic role as a buffer stock at the village level. This method is suitable is in the format of coaching and / or community service as well as facilitating forums organized jointly involving the mayor and 12 villages and communities as key stakeholders in the management of food security. Application of food stock management in the village Pabelan expected to have implications for government policy Pabelan significant village, namely: (i) Optimizing the management of ‘treasury village land for food (rice) for people (households) in the Village Pabelan, (ii) Efficiency Pabelan rice farm in the village in order to increase income of rice farmers in the village Pabelan, (iii) Strengthening the coordination of management of the stocks (reserves) in the Village Pabelan food through the village barn (LLP), Village, and (iv) The management of food reserves in a sustainable manner so as to ensure the formation of food sovereignty (production, availability and access to food) in the Village Pabelan.